Evaluation of the Three‐Dimensional Translational and Angular Deformity in Slipped Capital Femoral Epiphysis. Issue 5 (10th December 2019) - Bland, Daniel C.; Valdovino, Alan G.; Jeffords, Megan E.; Bomar, James D.; Newton, Peter O.; Upasani, Vidyadhar V.
Abstract : ABSTRACT: The purpose of this study was to quantify three‐dimensional translational and angular deformity (defined as theta) present at the proximal femoral physis in slipped capital femoral epiphysis (SCFE), and to use theta to differentiate between SCFE hips, contralateral unaffected hips, and normal hips by comparing to the current gold standard measure of the Southwick slip angle (SSA). 3DCT reconstructions of the pelvis and femur in SCFE patients and normal adolescents were obtained and pelvic position was standardized. The center point and direction vector of the femoral epiphysis was determined. The femoral neck axis was defined. The angle between the femoral neck axis and epiphysis vector defined the 3D angle of deformity (theta). The 3D translation of the femoral epiphysis, measured as a percentage of femoral neck diameter, was measured in three planes. The average theta angle was significantly greater in SCFE hips (46.5 ± 24.3°) compared with control (13.7 ± 6.4°) or normal (11.7 ± 3.7°) hips ( p < 0.001). There was no significant difference in theta angle between control and normal hips ( p = 0.468). Theta angle correlated strongly with SSA ( rs = 0.737, p < 0.001). Statement of clinical significance: The proximal femoral deformity in patients with slipped capital femoral epiphysis can be defined by measuring displacement of the epiphysis in all three dimensions in relation to the femoral neck axis. This information can be used in epiphyseal reorientation surgery to ensure anatomic reduction. The similarity between control and normal hips may argue against the thought that there is pre‐existing deformity in a pre‐slip condition of unaffected contralateral hips in SCFE patients. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:1081‐1088, 2020